Pembelajaran Musik Tradisional Gorontalo: Studi tentang Teknik Dasar Polopalo dan Implikasinya terhadap Perkembangan Kognitif pada Siswa Kelas VII SMP Negeri 1 Tilong Kabila - Ohi, Rahmawati (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to describe the learning process of Gorontalo traditional music, focusing on the basic techniques of the Polopalo instrument, and analyze its implications for the cognitive development of seventh-grade students at SMP Negeri 1 Tilong Kabila. This research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results showed that learning Polopalo not only introduced students to local wisdom and cultural preservation but also had positive impacts on cognitive aspects, particularly in improving concentration, motor coordination, memory, and problem-solving skills. The implications of this study are expected to serve as a foundation for developing local content curricula based on Gorontalo traditional arts at the junior high school level.Pembelajaran Musik Tradisional Gorontalo: Studi tentang Teknik Dasar Polopalo dan Implikasinya terhadap Perkembangan Kognitif pada Siswa Kelas VII SMP Negeri 1 Tilong Kabila